Role of HtrA in the Virulence and Competence of Streptococcus pneumoniae - Ibrahim, Yasser Musa (American Society for Microbiology, 2004)
HtrA is a major virulence factor of Streptococcus pneumoniae (the pneumococcus). Deletion of the gene for HtrA from strain D39 of the pneumococcus completely abolished its virulence in mouse models of pneumonia and bacteremia, while the virulence of a second strain (TIGR4) was dramatically reduced. HtrA-negative mutants induced much less inflammation in the lungs during pneumonia than the wild type. HtrA is involved in the ability of the pneumococcus to grow at high temperatures, to resist oxidative stress, and to undergo genetic transformation. The expression and cellular location of several known virulence factors of the pneumococcus were not affected by the lack of HtrA.